Building a customized module for the treatment of drug addiction under the remedial programs to be implemented on inmates at the drug rehabilitation centers in Malaysia - Ahmad, Jamaludin; Sulaiman, Tajularipin; Abdullah, Saifuddin Kumar; Shamsuddin, Junaidi (David Publishing Company, 2009)
The purpose of this study was to build a customized module for the treatment of drug addiction under the remedial program to be implemented on inmates at the drug rehabilitation centers in Malaysia. The centers were operated by the National Anti-Drug Agency (Agensi Anti Dadah Kebangsaan, AADK) under the Ministry of Home Affairs. The research design used was a descriptive study. The building of the module involved nineteen personnel, comprised of an Anti-Drug Special Officer from the State of Selangor Department of Education, nine Anti-Drug Special Officers, each from the nine District Offices of Education and nine selected school counselors, each representing their districts. The model used as reference in the building of the module was Russell’s model (1974). The results showed that model proposed by Russell (1974) was suitable to be used in the building of the module. Finally, several suggestions and/or recommendations were given at the end of this research report. The report ended with the concluding remarks.